2012
DOI: 10.1159/000338034
|View full text |Cite
|
Sign up to set email alerts
|

Use of Activated Recombinant Factor VII in Severe Bleeding – Evidence for Efficacy and Safety in Trauma, Postpartum Hemorrhage, Cardiac Surgery, and Gastrointestinal Bleeding

Abstract: Background: Uncontrolled bleeding continues to be a major cause of mortality in trauma, cardiac surgery, postpartum hemorrhage and liver failure. The aim of this paper is to assess the evidence supporting the efficacy of activated recombinant factor VII (rFVIIa) administration in these settings. Methods: Electronic literature search. Results: Numerous retrospective trials have mostly shown a decrease in blood transfusion requirements with no increase in thromboembolic events (TEE), but major limitations in tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A study reported thrombosis as an adverse effect following its use in cardiac surgery however its occurrence in obstetric practice is rare. 24…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…A study reported thrombosis as an adverse effect following its use in cardiac surgery however its occurrence in obstetric practice is rare. 24…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…The recombinant activated factor VII (FVII, rFVIIa, FXIII), prothrombin complex concentrates (PCC) and antifibrinolytics (tranexamic acid, epsilon aminocaproic acid and aprotinin) have been used for the management of traumatic bleeding [110] and found to produce a reduction in RBC use but not necessarily improvement in mortality. More recently, viscoelastic assays (rotational thromboelastometry -ROTEM or thromboelastography-TEG) have been advocated [111]. Early recognition of a coagulopathy and subsequent monitoring is vital to both initiate and maximize resuscitation therapy.…”
Section: Implementing Evidence-based Best Practices In the Management...mentioning
confidence: 99%
“…In these studies, rFVIIa was given for MOH of different etiology, at different doses and at non-uniform intervals [83,84]. Also, administration of rFVIIa has the potential disadvantage of causing serious thromboembolism in the obstetric population when administered during massive hemorrhage [85,86]. Given the lack of data supporting the use of rFVIIa, its high cost, and the side effects described above, it is hard to support its routine use for treatment of major obstetric hemorrhage.…”
Section: Fibrinogen Concentrate/cryoprecipitatementioning
confidence: 99%